AN X-RAY ABSORPTION FINE STRUCTURE AND NUCLEAR MAGNETIC RESONANCE SPECTROSCOPY STUDY OF GALLIUM - SILICA COMPLEXES IN AQUEOUS SOLUTION - Pokrovski G.S.; Schott J.; Pokrovsky O.S.; Hazemann J.-L.; Farges F. (My University, 2002)
The influence of aqueous silica on gallium(III) hydrolysis in dilute (2 × 10−4 ≤ mGa ≤ 5 × 10−3) and moderately concentrated (0.02 ≤ mGa ≤ 0.3) aqueous solutions was studied at ambient temperature, using high resolution X-ray absorption fine structure (XAFS) and nuclear magnetic resonance (NMR) spectroscopies, respectively. Results show that, in Si-free acidic solutions (pH < 3), Ga is hexa-coordinated with oxygens of H2O molecules and/or OH groups in the first coordination sphere of the metal. With increasing pH, these hydroxyl groups are progressively replaced by bridging oxygens (–O–), and polymerized Ga–hydroxide complexes form via Ga–O–Ga chemical bonds. In the 2.5–3.5 pH range, both XAFS and NMR spectra are consistent with the dominant presence of the Ga13 Keggin polycation, which has the same local structure as A113. Under basic pH (pH > 8), Ga exhibits a tetrahedral coordination, corresponding to Ga(OH)4− species, in agreement with previous NMR and potentiometric studies. Major changes in Ga hydrolysis have been detected in the presence of aqueous silica. Ga is tetra-coordinated, both in basic and acid (i.e., at pH > 2.7) Si-bearing solutions (0.01 ≤ mSi ≤ 0.2), and forms stable gallium–silicate complexes. In these species, Ga binds via bridging oxygen to 2 ± 1 silicons, with an average Ga–Si distance of 3.16 ± 0.05 Å, and to 2 ± 1 silicons, with an average Ga–Si distance of 3.39 ± 0.03 Å. These two sets of Ga–Si distances imply the formation of two types of Ga–silicate aqueous complex, cyclic Ga–Si2–3 species (formed by the substitution of Si in its tri-, tetra- or hexa-cyclic polymers by Ga atoms), and chainlike GaSi2–4 species (similar to those found for A1), respectively. The increase in the number of Si neighbors (a measure of the complex concentration and stability), in alkaline media, with increasing SiO2(aq) content and decreasing pH is similar to that for A1–Si complexes found in neutral to basic solutions. At very acid pH and moderate silica concentrations, the presence of another type of Ga–Si complex, in which Ga remains hexa-coordinated and binds to the silicon tetrahedra via the GaO6 octahedron corners, has also been detected. These species are similar to those found for Al3+ in acid solutions. Thus, as for aluminum, silicic acid greatly hampers Ga hydrolysis and enhances Ga mobility in natural waters via the formation of gallium–silicate complexes.